2019
DOI: 10.1021/acscentsci.8b00826
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Salt-Enhanced Electrostatic Repulsion in Colloidal Crystal Engineering with DNA

Abstract: Realizing functional colloidal single crystals requires precise control over nanoparticles in three dimensions across multiple size regimes. In this regard, colloidal crystallization with programmable atom equivalents (PAEs) composed of DNA-modified nanoparticles allows one to program in a sequence-specific manner crystal symmetry, lattice parameter, and, in certain cases, crystal habit. Here, we explore how salt and the electrostatic properties of DNA regulate the attachment kinetics between PAEs. Counterintu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…This unexpected trend contrasts prior solution phase work, which showed that crystal size decreases with increasing concentration of PAEs. 19 In principle, the nucleation rate should increase with increasing PAE concentration, resulting in an increased number of crystals and overall lower crystal size. The observed lack of increase in nucleation rate for substrate-bound crystals is hypothesized to arise because the concentration of PAEs in solution vastly exceeds the concentration that has been demonstrated to saturate the substrate 20,21 ; this result was also corroborated using a twodimensional Johnson-Mehl-Avrami-Kolmogorov (JMAK) approach (see Supplementary Note 1 for calculations).…”
Section: Textmentioning
confidence: 99%
“…This unexpected trend contrasts prior solution phase work, which showed that crystal size decreases with increasing concentration of PAEs. 19 In principle, the nucleation rate should increase with increasing PAE concentration, resulting in an increased number of crystals and overall lower crystal size. The observed lack of increase in nucleation rate for substrate-bound crystals is hypothesized to arise because the concentration of PAEs in solution vastly exceeds the concentration that has been demonstrated to saturate the substrate 20,21 ; this result was also corroborated using a twodimensional Johnson-Mehl-Avrami-Kolmogorov (JMAK) approach (see Supplementary Note 1 for calculations).…”
Section: Textmentioning
confidence: 99%
“…[4,[12][13][14] Indeed, hundreds of crystals have been generated, spanning over 50 different crystal symmetries. [11,[15][16][17][18] Chemical parameters (e.g., core identity, [12,19,20] shell identity, [21,22] solvent, [18] pH, [23] salt concentration [24] ) have been widely used to control particle assembly; however, the influence of physical parameters on the crystallization process has not been fully explored, with temperature and irradiation wavelength and time (in the case of photo-sensitive PAEs) being primarily utilized to affect crystal growth. [25,26] In the case of magnetic particles, magnetism is a powerful tool that can be used to influence crystal growth.…”
mentioning
confidence: 99%
“…Our capability to measure facet-dependent interfacial stiffness and our demonstration on their role in shaping the supracrystals can advance crystal design at the nanoscale. For example, one can control the interfacial stiffness and crystal habit by utilizing the toolkits of both intrinsic parameters of NP shape and surface chemistry 41 , 54 56 as well as extrinsic parameters, such as temperature, pH, and ionic strength 57 59 . Previously reports have shown that changing the length of DNA ligands on the same gold NPs has led to tunability in the lattice symmetry of the interior structure and exposed facets of the supracrystal 17 , 55 , 60 .…”
Section: Discussionmentioning
confidence: 99%